Pengaruh Shopee Terhadap Minat Beli Kaum Lelaki pada Mahasiswa Ilmu Komunikasi di Universitas Medan Area - Hindepeya, Mitra; Barus, Rehia K. Isabella; Matondang, Armansyah (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2024)
This study aims to determine the impact of using the Shopee application on men's buying interest among students majoring in Communication Studies at Medan Area University. In the well-known context that online shopping is generally dominated by women, this study shows that men are also active in such activities. The research method used was quantitative descriptive with purposive sampling samples, collecting data through a Google Form questionnaire filled out by 68 male students majoring in Communication Studies at Medan Area University. The results showed that 28.1% of men's buying interest variance could be explained by the use of the Shopee application, while 71.9% was influenced by other factors. A simple linear regression analysis yielded a calculated t value of 5.074, exceeding the table's t of 1.670. This confirms that there is a significant influence between the use of the Shopee application and men's buying interest, by rejecting the null hypothesis and accepting alternative hypotheses.